Muertes silenciadas: Problemática del suicidio en los campesinos de La Unión (Antioquia) (2014)
ABSTRACT: Over the last two decades the problem of suicide among the Colombian peasant farmer population has seen a marked increase. Objective: to explain the social components that contribute to recurring suicidal behavior in certain rural populations though a case study of the La Union (Antioquia) municipality, the suicide rates of which have been evidently higher during this period at over 20 in every thousand inhabitants, while the national rate fluctuates between 4 and 5. Methodology: quantitative and qualitative methodological strategies were used with the aim of making a comprehensive reading of the problem (suicide rates between 1990 and 2000, surveys, interviews and ethnography). The sociological analysis was privileged, that of understanding suicide as a collective phenomenon that depends on certain social conditions and subjective appropriations. Results and discussion: the following social dimensions that characterize the phenomenon were attained: (a) the intensification of the neo-liberal model which has devastated the local farming economy; (b) the exacerbation of the armed conflict which has destructured social life; (c) the vulnerability of peasant youth, those most affected by the deficiencies of country life; (d) the subjectivities of gender apparent in inverse suicidal behavior: more men commit suicide while more women attempt it.